TAome analysis of type-II toxin-antitoxin system from Xenorhabdus nematophila. (October 2018) - Yadav, Mohit; Rathore, Jitendra Singh
Graphical abstract: Highlights: First essentially complete TAome analysis for type II toxin-antitoxin systems. A comparative TAome study with Photorhabdus luminescens. Comprehensive evolutionary relationship of toxins from Xenorhabdus nematophila . Functional and transcriptional charaterization of relBE TA module. Give a new sight for rid of multi-drug tolerance in bacterial population. Abstract: Here we report the first essentially complete TAome analysis for type II toxin-antitoxin (TA) system, a major class of TA modules found in bacterial system, from entomopathogenic bacterium Xenorhabdus nematophila ATCC 19061 (NCBI RefSeq NC_014228). We summarize this analysis in terms of TA locus, accession identifier, hits in conserved domain database, toxin superfamily, antitoxin superfamily and chromosomal/mobile genome/plasmid occurrences. Moreover, for TA context analyses we use six different specifications namely virulence factors, mobile genetic elements (MGE), antibiotic resistance genes, secretion systems, prophage and a classification of mobile genetic elements (ACLAME); among these hits are found for only MGE, ACLAME and prophage. A total 39 sets of TA have been discovered in which numbers of TA encoded for MGE, ACLAME and prophage are 15, 15 and 5 respectively while the remaining four have no context hit. In addition, a comparative analysis of TAome was also done with closely related bacterium Photorhabdus luminescens subsp . laumondii TTO1 (NCBI RefSeq NC_005126) and results shows that a total 8 sets of TA are conserved. Further, a bootstrap Neighbor-Joining phylogenetic tree was also constructed for major toxin protein superfamily found namely RelE, HigB, GNAT, CcdB and MazF explored in the TAome of X. nematophila . We also characterized, the most abundantly found TA module ( relBE ) in this TAome, functionally and transcriptionally. This first TAome analysis of type II TA modules provides new insights in multi-drug tolerance in bacterial populations.